Solanesyl diphosphate synthase, an enzyme of ubiquinone synthetic pathway, is required throughout the life cycle of Trypanosoma brucei - De Hua, Lai (2014)
Ubiquinone 9 (UQ9), the expected product of the long-chain solanesyl diphosphate synthase of Trypanosoma brucei (TbSPPS), has a central role in reoxidation of reducing equivalents in the mitochondrion of T. brucei. The ablation of TbSPPS gene expression by RNA interference increased the generation of reactive oxygen species and reduced cell growth and oxygen consumption. The addition of glycerol to the culture medium exacerbated the phenotype by blocking its endogenous generation and excretion. The participation of TbSPPS in UQ synthesis was further confirmed by growth rescue using UQ with 10 isoprenyl subunits (UQ10). Furthermore, the survival of infected mice was prolonged upon the downregulation of TbSPPS and/or the addition of glycerol to drinking water. TbSPPS is inhibited by 1-[(n-oct-1-ylamino)ethyl] 1,1-bisphosphonic acid, and treatment with this compound was lethal for the cells. The findings that both UQ9 and ATP pools were severely depleted by the drug and that exogenous UQ10 was able to fully rescue growth of the inhibited parasites strongly suggest that TbSPPS and UQ synthesis are the main targets of the drug. These two strategies highlight the importance of TbSPPS for T. brucei, justifying further efforts to validate it as a new drug target